Surgical injury: comparing open surgery and laparoscopy by markers of tissue damage - Máca, Jan; Peteja, Matúš; Reimer, Petr; Jor, Ondřej; Šeděnková, Věra; Panáčková, Lucie; Ihnát, Peter; Burda, Michal; Ševčík, Pavel (Therapeutics and clinical risk management, 2018)
BACKGROUND: Major abdominal surgery (MAS) is high-risk intervention usually accompanied by tissue injury leading to a release of signaling danger molecules called alarmins. This study evaluates the surgical injury caused by two fundamental types of gastrointestinal surgical procedures (open surgery and laparoscopy) in relation to the inflammation elicited by alarmins. PATIENTS AND METHODS: Patients undergoing MAS were divided into a mixed laparoscopy group (LPS) and an open surgery group (LPT). Serum levels of alarmins (S100A8, S100A12, HMGB1, and HSP70) and biomarkers (leukocytes, C-reactive protein [CRP], and interleukin-6 [IL-6]) were analyzed between the groups. The secondary objectives were to compare LPT and LPS cancer subgroups and to find the relationship between procedure and outcome (intensive care unit length of stay [ICU-LOS] and hospital length of stay [H-LOS]). RESULTS: A total of 82 patients were analyzed. No significant difference was found in alarmin levels between the mixed LPS and LPT groups. IL-6 was higher in the LPS group on day 2 (p=0.03) and day 3 (p=0.04). Significantly higher S100A8 protein levels on day 1 (p=0.02) and day 2 (p=0.01) and higher S100A12 protein levels on day 2 (p=0.03) were obtained in the LPS cancer subgroup. ICU-LOS and H-LOS were longer in the LPS cancer subgroup. CONCLUSION: The degree of surgical injury elicited by open MAS as reflected by alarmins is similar to that of laparoscopic procedures. Nevertheless, an early biomarker of inflammation (IL-6) was higher in the laparoscopy group, suggesting a greater inflammatory response. Moreover, the levels of S100A8 and S100A12 were higher with a longer ICU-LOS and H-LOS in the LPS cancer subgroup.
Keywords: gastrointestinal surgery; laparoscopy; open surgery; major surgery; surgical injury; alarmins